PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD), PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kota Depok) - As Syifa Nurillah; Dul Muid (Diponegoro Journal of Accounting, 2014)
This research was conducted to determine the factors that affect the quality of local government financial reports . The factors studied were the effects of Human Resources competencies , the application of Financial Accounting System , the utilization of information technology , and Internal Control System .Collecting data this research used a questionnaire survey. The questionnaire was delivered to 100 employees working units (SKPD ) Depok city in financial/ accounting division, total of 64 questionnaires ( 64 % ) returned complete and can be processed . The data collected were processed using SPSS version 21.0. The statistical methods used to test the hypotheses is multiple linear regression analysis. The results of hypothesis testing is human resource competency, Local Financial Accounting System implementation, utilization of information technology, and systems of internal control the government has a significant positive effect on the quality of local government financial reports..